Aktivitas Antibakteri Minyak Atsiri Daun Tembakau terhadap Pertumbuhan Bakteri Escherichia coli dan Staphylococcus aureus - Nurnasari, Elda; Wijayanti, Kristiana Sri (Jurnal Kefarmasian Indonesia, 2019)
Tobacco plants are widely used as raw material for cigarettes, but the results of the study show that in tobacco leaves contain compounds that can be used in the pharmaceutical and health fields. Tobacco leaves contain essential oils that have a distinctive aroma. The study aims to examine the antibacterial activity of tobacco essential oil from six sources tobacco such as Temanggung, Yogyakarta, Purwodadi, Boyolali, Blitar and Probolinggo. Tobacco essential oil is obtained by the steam-water distillation method. Antibacterial activity evaluation was carried out by diffusion method and the minimum inhibitory concentration on two bacteria, Escherichia coli and Staphylococcus aureus. The yield of tobacco essential oil ranged from 0.54-3.39%. Tobacco essential oil had antibacterial activity against bacteria E. coli and S. aureus in the presence of inhibition zones in bacterial media. The biggest inhibition zone was in Yogyakarta tobacco essential oil of 26 mm for S. aureus bacteria, while for E. coli bacteria the biggest inhibition zone was Blitar tobacco essential oil which was equal to 21 mm. The inhibition zone was not much different from the inhibition zone in tetracycline antibiotic testing (positive control) which was 25 mm in S. aureus and 21.5 mm bacteria in E. coli bacteria. Tobacco essential oil from Probolinggo was able to inhibit the growth of S. aureus bacteria up to a concentration of 6.25% and E. coli bacteria to a concentration of 12.5%.